Decreased IP-10 and Elevated TGFβ1 Levels are Associated with Viral Clearance Following Therapy in Patients with Hepatitis C Virus. Issue 5 (30th May 2013) - Lee, Silvia; Varano, Julius; Flexman, James P.; Cheng, Wendy; Watson, Mark W.; Rossi, Enrico; Adams, Leon A.; Bulsara, Max; Price, Patricia
Abstract : The role of pro-fibrogenic cytokines in the outcome of infections with hepatitis C virus (HCV) and the response to treatment with pegylated interferon-alpha (pegIFN α ) and ribavirin remains unclear. To address this issue, we assessed hepatic fibrosis and plasma markers pertinent to T-cell mediated fibrogenesis and inflammation at the start of treatment. Levels of soluble (s)CD30, interleukin-13 receptor alpha 2 (IL-13R α 2), total and active transforming growth factor-beta 1 (TGF β 1), interleukin-18 (IL-18) and interferon-gamma inducible protein-10 (IP-10, CXCL10) were correlated with the severity of fibrosis and with treatment outcome using multiple logistic regression modelling. The Hepascore algorithm was confirmed as a marker of fibrosis, but was a poor predictor of treatment outcome. Inclusion of all immunological markers improved prediction based on Hepascore alone ( p = 0.045), but optimal prediction was achieved with an algorithm ("TIPscore") based on TGF β 1 (total), IP-10, age, sex and HCV genotype ( p = 0.003 relative to Hepascore). Whilst this was only marginally more effective than predictions based on HCV genotype age and sex ( p = 0.07), it associates high TGFβ1 and low IP-10 levels with a failure of therapy.